Composition of Dissolved Organic Matter in Pore Waters of Anoxic Marine Sediments Analyzed by 1H Nuclear Magnetic Resonance Spectroscopy - Fox, Christina A.; Abdulla, Hussain A.; Burdige, David J.; Lewicki, James P.; Komada, Tomoko (Frontiers in Marine Science, 2018)
Marine sediments are globally significant sources of dissolved organic matter (DOM) to the oceans, but the biogeochemical role of pore-water DOM in the benthic and marine carbon cycles remains unclear due to a lack of understanding about its molecular composition. To help fill this knowledge gap, we used 1H nuclear magnetic resonance (NMR) spectroscopy to examine depth variability in the composition of pore-water DOM in anoxic sediments of Santa Barbara Basin, California Borderland. Proton detected spectra were acquired on whole samples without pre-concentration to avoid preclusion of any DOM components from the analytical window. Broad unresolved resonance (operationally assigned to carboxyl-rich alicyclic molecules, or CRAM) dominated all spectra. Most of the relatively well-resolved peaks (attributed to biomolecules or their derivatives) appeared at chemical shifts similar to those previously reported for marine DOM in the literature, but at different relative intensities. DOM composition changed significantly within the top 50 cm of the sediment column, where the relative intensity of CRAM increased, and the relative intensity of resolved resonances decreased. The composition of CRAM itself also changed throughout the entire length of the 4.5-m profile, as CRAM protons became increasingly aliphatic at the expense of functionalized protons. Given that pore-water DOM is generated from sedimentary organic matter that includes pre-aged and degraded material, and that DOM could theoretically be subjected to microbial reworking in the pore waters for centuries to millennia, these data suggest that marine sediments may be sources of CRAM that are compositionally unique from CRAM generated in the upper ocean.